Meta-Analysis: Drug Side Effect, Smoking, Alcohol Consumptions and Their Relationships with Drug Taking Adherence in Tuberkulosis Patients - Aem Ismail; Hanung Prasetya; Burhannudin Ichsan (Masters Program in Public Health, 2023)
Background: Inappropriate tuberculosis treatment is a major determinant of multidrug-resistant tuberculosis (MDR) TB, which is related to patient adherence to treatment. There are several factors that affect MDR-TB such as drug side effects, smoking and alcohol consumption. The aim is to estimate the magnitude of the effect of drug side effects on tuberculosis treatment adherence, based on the results of a number of similar primary studies.Subjects and Method: This study is a systematic review and meta-analysis research. Article search was carried out based on the eligibility criteria of the PICO model including: P= Tuberculosis patient; I= drug side effects, smoking and alcohol consumption; C= no drug side effects, no smoking and no alcohol consumption; O= Tuberculosis treatment adherence. Articles were collected from Google scholar, PubMed, Science Direct, and Springerlink. Keywords using “drug side effects” OR “tobacco smoking” OR “alcohol consumption” OR “tuberculosis” AND “medication adherence” AND “cross sectional” AND “adjusted odds ratio”. Inclusion criteria in this study included articles with a cross-sectional study design, the relationship size used was the adjusted Odds Ratio (aOR), articles published in the 2009 to 2022 range. Selected articles were tested for eligibility using CEBM and analyzed using the PRISMA diagram and the Review Manager 5.3 application.Results: 14 Cross-sectional studies were selected for the meta-analysis of 8 studies with 2,045 TB patients showed that drug side effects reduced TB treatment adherence by 0.26 times than no drug side effects (aOR= 0.26; 95% CI= 0.14 to 0.49; p< 0.001). 7 studies with 2,966 TB patients showed that alcohol consumption decreased TB treatment adherence by 0.61 times than not consuming alcohol (aOR= 0.61; 95% CI= 0.32 to 1.16; p= 0.130). Study 6 with 1,748 TB patients showed that smoking decreased TB treatment adherence by 0.86 times than non-smokers (aOR= 0.86; 95% CI= 0.17 to 4.37; p= 0.850).Conclusion: Side effects of drugs, alcohol, and smoking reduce treatment adherence in tuberculosis patients. Keywords: drug side effects, alcohol consumption, smoking, treatment adherence Correspondence: Aem Ismail. Master’s Program in Public Health, Universitas Sebelas Maret. Jl. Ir. Sutami 36A, Surakarta, Central Java, Indonesia. Email: aem.ismail80@gmail.com. Mobile: +6282133114822.